2009
DOI: 10.1063/1.3075952
|View full text |Cite
|
Sign up to set email alerts
|

Mean free path effects in the shock-implosion problem

Abstract: The effects of finite Knudsen number in the problem of a cylindrically imploding shock wave in a monatomic gas are investigated. Numerical solutions of the flow field are obtained with initial conditions in the ranges 1.25Յ M 0 Յ 5 and 0.005Յ Kn 0 Յ 0.1 using the direct simulation Monte Carlo method. Results show that as Kn 0 decreases and M 0 increases, the maximum implosion temperature scales increasingly well with the similarity exponent predicted in the Guderley solution for an imploding strong shock in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This also applies to the hydrodynamic case. 27 Second, for the hydrodynamic and magnetic Reynolds numbers we use density, velocity, and length scales as those immediately downstream of the shock, ρ and u, and the shock radius R s , respectively. Both Reynolds numbers are proportional to the product of these three scales.…”
Section: B Comparison Of Numerical Solution With Shock Dynamicsmentioning
confidence: 99%
“…This also applies to the hydrodynamic case. 27 Second, for the hydrodynamic and magnetic Reynolds numbers we use density, velocity, and length scales as those immediately downstream of the shock, ρ and u, and the shock radius R s , respectively. Both Reynolds numbers are proportional to the product of these three scales.…”
Section: B Comparison Of Numerical Solution With Shock Dynamicsmentioning
confidence: 99%
“…The equation of state for non-ideal gas was considered as given by Landau and Lifshitz [35]. The general characteristic rule for the propagation velocity (23) - (27), respectively. The change in entropy  s across the imploding shock front in the non-ideal gas is given by the Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The flow field behind the converging shock waves was investigated in van der Waals gas by Wu and Roberts [24,25] and Evans [26]. Using the direct simulation Monte Carlo (DSMC) method, Goldsworthy and Pullin [27] investigated the effects of finite Knudsen number in the problem of a cylindrically imploding shock wave and found that the solution of the dissipative flow field displays a scaling consistent with the Guderlay similarity exponent. Kjellander, Tillmark and Apazidis [28] studied strong cylindrical and spherical shock implosion in a monatomic real gas and shown that ionization has a major effect on temperature and density behind the converging shock as well as on the shock acceleration.…”
Section: Introductionmentioning
confidence: 99%